2016
DOI: 10.1007/s00408-016-9906-z
|View full text |Cite
|
Sign up to set email alerts
|

A scoring system for predicting the survival prognosis of patients receiving stereotactic body radiation therapy (SBRT) for 1–3 lung metastases

Abstract: A survival scoring system for patients receiving SBRT for very few lung metastases was developed. This score allowed us to estimate the survival prognosis of these patients and can aid physicians when aiming to choose the optimal SBRT dose for individual patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…We showed a benefit in OS for patients with a KPS ≥90%, small GTV and PTV, higher BED doses, absence of external metastases, ≤3 pulmonary metastases, and a controlled primary tumor. This prognostic impact could also be shown by other studies [6,7,25,27,30,31].…”
Section: Discussionsupporting
confidence: 80%
“…We showed a benefit in OS for patients with a KPS ≥90%, small GTV and PTV, higher BED doses, absence of external metastases, ≤3 pulmonary metastases, and a controlled primary tumor. This prognostic impact could also be shown by other studies [6,7,25,27,30,31].…”
Section: Discussionsupporting
confidence: 80%
“…Thus, the treatment of a very limited number of brain metastases has become more complex recently and requires more personalized treatment regimens. Such a personalized treatment approach should always consider a patient's survival prognosis, which has been suggested for other metastatic situations (7)(8)(9)(10)(11)(12)(13)(14). In order to facilitate the selection of the appropriate treatment regimen for a patient who is supposed receiving radiosurgery or fractionated stereotactic radiotherapy (FSRT) alone for a very limited number of brain metastases, a scoring-system that allows the physician to quickly estimate a patient's remaining survival time is helpful.…”
mentioning
confidence: 99%
“…On the multivariate analysis of the previous study, three factors were found to be significantly associated with survival. These factors were age at the time of radiotherapy (≤60 versus ≥61 years), Eastern Cooperative Oncology Group (ECOG) performance score (0-1 versus 2) and extra-cranial metastases (no versus yes) (12). For each of these three factors, the 1-year survival rates in % were divided by 10, and subsequently, the three scoring-points were summed to generate the prognostic score for a specific patient.…”
mentioning
confidence: 99%
“…Our initial search yielded 693 potentially relevant citations. After screening was completed, a total of 13 studies with 559 patients were eligible for inclusion after screening 7–19 . A PRISMA flow diagram is provided to outline the selection process (Figure 1).…”
Section: Resultsmentioning
confidence: 99%